Modelos bayesianos para análise de características reprodutivas de fêmeas Nelore - Garcia, Diogo Anastácio [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Reproductive traits are very important to beef cattle production system and, some of them, such as age at first calving (AFC), days to calving (DC), and longevity (LONG) are easy to measure and do not bring further measurement costs to the production system. However, these reproductive traits show low heritabilities and, one of the reasons might be the fact that only fertile females have phenotypic records, because when the genetic evaluation is performed some cows have missing records due to reproductive failure, as well as due to voluntary and involuntary culling, which are made before the breeding season, and, in some cases, due to inconsistent phenotypic informations. These partially or unobserved phenotypes are termed as censored records. According to some studies, properly accounting for censored records in genetic analysis could avoid distorted inferences and better genetic breeding value predictions. Several methodologies have been proposed to cope with censored records in genetic evaluations, such as models in which censored records are penalized, Bayesian hierarchical models to deal with censored data, threshold-linear models, and frailty survival models. However, these approaches have not been widely applied in Brazil. The objectives of this study were to evaluate age at first calving, days to calving, and longevity, of the Nellore breed females, applying models which handle phenotypic informations as uncensored and censored, aiming to find appropriate models to genetic evaluation for these traits. Data were provided by Nellore Alianca and reproductive records of animals born from 1993 to 2007, in farms located in south-east and middle-west of Brazil, were considered in the study. Contemporary groups (CG) for AFC were defined by the combination of farm, month, and year of birth, farm and management group at weaning, and farm and management group at long-yearling. For DC and LONG ...

As características reprodutivas são importantes para o sistema produtivo de carne bovina e, algumas delas, como a idade ao primeiro parto (IPP), dias para o segundo parto (DPP) e longevidade produtiva (LONG), são de fácil mensuração e não oneram o sistema produtivo para a obtenção fenotípica de sua expressão. Porém, estas características reprodutivas apresentam herdabilidade de baixa magnitude e, uma das razões, pode ser o fato de estas serem mensuradas apenas nas fêmeas consideradas férteis, pois no momento da avaliação genética, uma porção das fêmeas, normalmente, não apresentam fenótipos devido a falhas reprodutivas, descarte voluntário e involuntário anterior à estação de monta e, em alguns casos, por registros inconsistentes. Estes registros parciais ou desconhecidos são denominados informações censuradas. De acordo com alguns estudos, a inclusão adequada das informações censuradas poderiam evitar distorções nas inferências e melhoria na predição dos valores genéticos. Algumas metodologias têm sido utilizadas para lidar com a censura nas avaliações genéticas como modelos com penalização, modelos hierárquicos Bayesianos para dados censurados, modelo linear-limiar e o de análise de sobrevivência. Porém no Brasil, essas abordagens não vêm sendo muito utilizadas. Este estudo tem como objetivo avaliar as características reprodutivas de idade ao primeiro parto, dias para o segundo parto e longevidade produtiva, de fêmeas da raça Nelore, utilizando modelos que tratam as expressões fenotípicas destas características como não censuradas e censuradas, com a finalidade de encontrar modelos adequados para avaliação genética dos animais para estas características. Foram utilizadas fêmeas nascidas entre 1993 a 2007, da região sudeste e centro-oeste do Brasil, as quais fazem parte da base de dados Aliança Nelore. Para IPP, os grupos de ...
Keywords: Bovino de corte; Bovino - Reprodução; Nelore (Zebu); Longevidade; Idade; Longevity